Regeneration of antigen-specific T cells by using induced pluripotent stem cell (iPSC) technology. (18th October 2021) - Kawamoto, Hiroshi; Masuda, Kyoko; Nagano, Seiji
Abstract: In currently ongoing adoptive T-cell therapies, T cells collected from the patient are given back to the patient after ex vivo cell activation and expansion. In some cases, T cells are transduced with chimeric antigen receptor (CAR) or T-cell receptor (TCR) genes during the ex vivo culture period. Although such strategies have been shown to be effective in some types of cancer, there remain issues to be solved; these methods (i) are time-consuming, (ii) are costly and (iii) it is difficult to guarantee the quality because the products depend on patient-derived T cells. To address these issues, several groups including ours have developed methods in which cytotoxic cells are mass-produced by using induced pluripotent stem cell (iPSC) technology. For the regeneration of T cells, the basic idea is as follows: iPSCs produced from T cells inherit rearranged TCR genes, and thus all regenerated T cells should express the same TCR. Based on this idea, various types of T cells have been regenerated, including conventional cytotoxic T lymphocytes (CTLs), γδT cells, NKT cells and mucosal-associated invariant T (MAIT) cells. On the other hand, any cytotoxic cells can be used as the base cells into which CAR is introduced, and thus iPSC-derived NK cells have been developed. To apply the iPSC-based cell therapy in an allogeneic setting, the authors' group developed a method in which non-T-cell-derived iPSCs are transduced with exogenous TCR genes (TCR-iPSC method). This approach is being prepared for a clinical trial to be realized in Kyoto University Hospital, in which acute myeloid leukemia patients will be treated by the regenerated WT1 antigen-specific CTLs. Graphical Abstract: